Cultivating Empathy through Communication: Understanding Others to Improve Relationships - Husain, Yasin (Journal of Public Representative and Society Provision, 2021)
This systematic literature review aims at exploring the effects of empathy in communication. This is because, as the review points out from major empirical studies, empathy is important in promoting prosocial behavior, improving ethical reasoning and improve interpersonal relations within and outside the health fields and education. Concerning the limitations of empathy, it finds that empathy is not immune to biases and empathic burnout, and, thus, requires a better understanding. Furthermore, the research highlights several directions for the future studies pointing out that future research must investigate how empathy is incorporated in various social media platforms and how multicultural communication tactics can be designed. Such findings are important to enhance the strength of empathy for the world that is becoming an increasingly globalized environment, which requires not only understanding and cooperation but also compassion to solve various social issues. The review establishes empathy as a viable approach in communication especially in an emergency.